SIMULASI IMPLEMENTASI RFID PADA SISTEM PARKIR MOTOR (Studi Kasus: Fakultas Teknik Univ. Muhammadiyah Jakarta) - Siti Alwya Syarif; Abd. Karman (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
RFID or Radio Frequency Identification, is a method which can be used to store or remotely retrieving data using devices called RFID tags or transponders. RFID tag is a small object, such as an adhesive sticker, and can be attached to an item or product. RFID tags contain antennas to enable them to receive and respond to a query that is emitted by an RFID transceiver. RFID is a wireless compact that superior technology to transform the commercial world. As the successor of the barcode, RFID can perform automatic control for many things. RFID systems offers improved efficiency in inventory control, logistics, and supply chain management.